Comparison of Frequency of Pseudo-Exfoliation Syndrome in Patients Undergoing Cataract Surgery in Different Regional Hospitals of Pakistan - Hussain, Irshad; Rauf, Abdul; Ishtiaq, Omar; Islam, Qamar-ul-; Khan, Faisal Aziz; Ali, Shahzad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the frequency of Pseudo-Exfoliation Syndrome (PXS) in patients undergoing cataract surgery in different regional hospitals in Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: Three Tertiary Care Hospitals of Karachi, Rawalakot and Skardu Pakistan, from Sep 2017 to May 2020.Methodology: Patients aged 45 years and more undergoing age-related cataract surgery were evaluated for Pseudo-Exfoliation Syndrome. Initially, each patient underwent a complete outpatient ophthalmological workup. Demographic details like age and gender were noted. All the patients were screened for hypertension and diabetes mellitus. In addition, patients were screened for pseudo-exfoliation syndrome. Congenital, developmental, secondary and traumatic cataracts were excluded.Results: A total of 1882 patients were included in the study. Pseudo-exfoliation was carried out in 249(13.23%) patients. In Hospital-A, 23(3.23%); in Hospital-B, 145(14.92%) and Hospital-C, 81(40.70%) of the patients had pseudo-exfoliation. The frequency of pseudo-exfoliation syndrome was significantly more in Hospital-C and then in Hospital-B and least in HospitalA (p